2013
DOI: 10.1002/dys.1468
|View full text |Cite
|
Sign up to set email alerts
|

WISC‐III Cognitive Profiles in Children with Developmental Dyslexia: Specific Cognitive Disability and Diagnostic Utility

Abstract: This study analyzed the usefulness of Wechsler Intelligence Scale for Children (WISC-III) in identifying specific cognitive impairments that are linked to developmental dyslexia (DD) and the diagnostic utility of the most common profiles in a sample of 100 Portuguese children (50 dyslexic and 50 normal readers) between the ages of 8 and 12. Children with DD exhibited significantly lower scores in the Verbal Comprehension Index (except the Vocabulary subtest), Freedom from Distractibility Index (FDI) and Proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
1
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 115 publications
2
16
1
3
Order By: Relevance
“…The results of this study are also inconsistent with the results of Moura O, Simoes MR, and Pereira M's studies, which were on the planning from executive function (25). In their study, there was no significant difference in planning between groups after comparing executive functions between children with learning disorders and normal children.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The results of this study are also inconsistent with the results of Moura O, Simoes MR, and Pereira M's studies, which were on the planning from executive function (25). In their study, there was no significant difference in planning between groups after comparing executive functions between children with learning disorders and normal children.…”
Section: Discussioncontrasting
confidence: 99%
“…In this study, the speed of processing, flexibility, planning, and fluidity of the word was studied in 50 children with reading disorders and 50 normal children between the ages of 8 and 12 in Portugal. After comparing the 2 groups, significant defects were observed in the processing speed, flexibility and fluidity of the word, while there was no significant difference in planning between the groups (25).…”
Section: Discussionmentioning
confidence: 89%
“…Several studies have found that children with DD showed deficits on both WISC-III Processing Speed Index subtests (Moura, Simões, & Pereira, 2014a;Thomson, 2003). Shanahan et al (2006) performed a detailed study that examined the presence of PS deficits in children and adolescents with DD and ADHD using a wide range of PS tasks.…”
Section: Processing Speedmentioning
confidence: 99%
“…For years, neurocognitive researchers have observed that children -4 -with DD performed extremely poorly on subtests corresponding to the current Working Memory Index of the Wechsler Intelligence Scale for Children (WISC) -Fourth Edition (ClercqQuaegebeur et al, 2010;Helland & Asbjornsen, 2004;Moura, Simões, & Pereira, 2013).…”
Section: Working Memory Impairments In Developmental Dyslexiamentioning
confidence: 99%